The Implementation of Mental Health Concept by Imam Al-Ghazali in Islamic Counseling Guidance - Hasan, Aliah B. Purwakania; Tamam, Abas Mansur (Journal of Strategic and Global Studies, 2018)
Nowadays, mental health issues are growing problems in the society. Many people experience a disruption in achieving ideal conditions in which they can live physically, mentally, spiritually, and socially healthy, but can also appreciate the potential that makes them productive. This study aims to discuss the mental health in Islamic perspective based on the thoughts of Imam Al-Ghazali. This study is a literature study using content analysis techniques. Mental health can be seen as a model consisting of the aqidah solidity, the liberation from the heart disease, the development of noble character, good morality built in social relations, and the achievement of happiness in the world and the hereafter. This article discusses the psychodynamics of Al-Ghazali that shows how humans fight the lust to become a better person. This article discusses the principles of mujahadah, riyadhah and tazkiyatun nafs methods to achieve mental health based on Imam al-Ghazali's thought, adjusted to the needs of counseling guidance. The various benefits of applied mental health concepts in counseling guidance are also described in this study.